Emotional Intelligence: Mengapa EI Lebih Penting daripada IQ? - Silvia Damayanti; Masduki Asbari; Dani Setiawan; Muhammad Sayup Saputra (Literaksi: Jurnal Manajemen Pendidikan, 2023)
This article is a critical reading of Daniel Goleman's inspiring and motivational guidebook "Emotional Intelligence: Why EI is More Important Than IQ." Daniel Goleman explores various interesting things about emotional intelligence. This study method is descriptive qualitative with content analysis techniques on the object of the book referred to above. From this book we can know that a high IQ does not guarantee one's success, why people with high IQ fail and people with IQ are becoming very successful. The cause is "emotional intelligence", which includes self-awareness and impulse control, perseverance, passion and self-motivation, empathy, and social skills. The good news is that emotional intelligence is not determined from birth. Because the emotional lessons a child learns shape his brain circuits, Goleman provides detailed guidelines on how we can shape emotional intelligence within us through his book Emotional Intelligence: Why EI is More Important Than IQ